2015
DOI: 10.1021/ja511444e
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Displacing DNA from Nanoceria: Mechanism and Detection of Glucose in Serum

Abstract: Hydrogen peroxide (H2O2) is a key molecule in biology. As a byproduct of many enzymatic reactions, H2O2 is also a popular biosensor target. Recently, interfacing H2O2 with inorganic nanoparticles has produced a number of nanozymes showing peroxidase or catalase activities. CeO2 nanoparticle (nanoceria) is a classical nanozyme. Herein, a fluorescently labeled DNA is used as a probe, and H2O2 can readily displace adsorbed DNA from nanoceria, resulting in over 20-fold fluorescence enhancement. The displacement me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
273
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 392 publications
(280 citation statements)
references
References 52 publications
(48 reference statements)
6
273
0
1
Order By: Relevance
“…Many MONPs (e.g., TiO2, CeO2, ITO) adsorb DNA mainly via the phosphate 10 backbone. 10,[12][13][14] Here, we confirmed that phosphate backbone binding is also important for DNA adsorption onto Cr2O3, Mn2O3 and ZnO. FAM-24 mer DNA (100 nM) in Buffer A to achieve fluorescence quenching (red spectra).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Many MONPs (e.g., TiO2, CeO2, ITO) adsorb DNA mainly via the phosphate 10 backbone. 10,[12][13][14] Here, we confirmed that phosphate backbone binding is also important for DNA adsorption onto Cr2O3, Mn2O3 and ZnO. FAM-24 mer DNA (100 nM) in Buffer A to achieve fluorescence quenching (red spectra).…”
Section: Resultssupporting
confidence: 67%
“…[1][2][3][4][5][6] While DNA has been interfaced with metal and carbon-based nanomaterials, [6][7][8][9] limited work was carried out on metal oxide nanoparticles (MONPs). [10][11][12][13][14][15][16][17][18][19][20] MONPs represent a very important class of material due to their unique electronic, optical, magnetic and catalytic properties. DNAfunctionalized MONPs might be useful as a sensor platform for anion detection.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Since then, nanoceria have been also found to exhibit CAT mimetic activity in some other studies. [16,22,35,[49][50][51] As CAT mimetics, nanoceria could catalyze the H 2 O 2 decompositon, with the final harmless products as water (H 2 O) and molecular oxygen (O 2 ). Pirmohamed et al [49] …”
Section: Mimetics Of Catalasementioning
confidence: 99%
“…[15] Other than those, the surface of nanomaterials may offer more catalytic sites while natural enzymes offer only one active site per molecule. [16] These enzyme mimetics have great value in practical applications, and therefore become a new frontier in inorganic, materials and analytical chemistry. [17][18][19] In previous studies, ceria nanoparticles (nanoceria) and nanoceria-supported materials have been reported to have multi-enzyme mimetic activities like those of superoxide oxidase, [20,21] catalase [22,23] and oxidase.…”
Section: Introductionmentioning
confidence: 99%
“…Since cerium is a hard metal that has a strong affinity to phosphate, 40,44,45 we propose that the phosphate group in the lipid might be playing a critical 12 role. To test this, we added free inorganic phosphate ions to the CeO2 NPs prior to mixing them with DOPC (Figure 3a).…”
mentioning
confidence: 99%